Transit Oriented Development in Medium Cities in Africa: Experiences from Kisumu, Kenya - Onyango, George M.; Owino, Fredrick O. (Journal of Geography and Regional Planning, 2021)
Transit Oriented Development (TOD) is a planned area with land use that has optimal reach of public transport by urban populace it serves. Availability and accessibility of public transport minimizes reliance of use by private users and this is the cardinal rule of TOD Principles have been developed that provide a framework for understanding TOD. Kisumu is used as a case study in exploring these principles and their validity in medium sized African city. The application of these principles in guiding city planning and development highlights how TOD can be an effective driver of sustainable urbanization. The paper presents the concept of TOD and then builds into the case study city: Kisumu. It enables the reader to contextualize the discussions in the subsequent sections. The paper then addresses TOD conceptualization. It looks at the broad categories of TOD that has been demonstrated in Kisumu as a result of the interventions of various actors. It finally looks at the challenges and opportunities that exist for TOD as a planning and development framework.
Keywords: Transportation; Densification; Accessibility; Sustainable Urban Development; Kisumu